2020
DOI: 10.1002/bit.27558
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of T7 RNA polymerase transcription enhances pET‐based recombinant protein production in Escherichia coli BL21 (DE3) by suppressing autolysis

Abstract: Escherichia coli BL21 (DE3) is an excellent and widely used host for recombinant protein production. Many variant hosts were developed from BL21 (DE3), but improving the expression of specific proteins remains a major challenge in biotechnology. In this study, we found that when BL21 (DE3) overexpressed glucose dehydrogenase (GDH), a significant industrial enzyme, severe cell autolysis was induced. Subsequently, we observed this phenomenon in the expression of 10 other recombinant proteins. This precludes a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…Here, most approaches are related to reducing recombinant gene expression, for example by decreasing gene copy numbers, promoter strength or inducer concentration e.g. [ 24 26 ]. The exact nature of the “disturbing impact” of enhanced recombinant gene transcription on cell growth is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…Here, most approaches are related to reducing recombinant gene expression, for example by decreasing gene copy numbers, promoter strength or inducer concentration e.g. [ 24 26 ]. The exact nature of the “disturbing impact” of enhanced recombinant gene transcription on cell growth is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…3D). Besides, E. coli BL21(DE3) strain usually suffered from cell autolysis (Wagner et al 2008;Narayanan et al 2008), which is obscure to control the right chance for cell harvest at the fermentation anaphase. Recombinant P. pastoris therefore exhibited great operation stability for fermentation process.…”
Section: Production Of Chmo Acineto -Mut Via High-density Fermentation On a 5-l Scalementioning
confidence: 99%
“…Studies had shown that when BL21 (DE3) overexpressed glucose dehydrogenase (GDH), an autolysable protein, severe cell autolysis was induced, resulting in low protein production [12]. Therefore, we investigated whether the three engineered strains can improve the expression of GDH through uorescence intensity (Fig.…”
Section: Application Of Engineered Host Strains In Gdh Productionmentioning
confidence: 99%
“…Recently, a gene growth switch based on CRISPRi was developed to achieve e cient production of target proteins by targeting genes related to cell growth and DNA replication in E. coli [11]. Sun et al constructed a non-autolytic strain capable of e ciently producing recombinant proteins by hybridizing the weak Lac promoter with the strong P LacUV5 [12]. On another hand, the P LacUV5 has a higher basic leakage expression, which cannot provide precise control of gene expression [13,14].…”
Section: Introductionmentioning
confidence: 99%